Bearing capacity of stabilised tropical peat by deep mixing method - Islam, Md. Shahidul; Hashim, Roslan (American-Eurasian Network for Scientific Information, Jordan, 2009)
Soft tropical peat has unique characteristics and poses serious problem in construction industry due to its low bearing capacity. Construction work over this problematic soil is not possible in its natural state. The paper represents the findings of a study into stabilisation of peat in Klang, Selengor, Dharul Ehsan, Malaysia using various types of binder by deep mixing method and its effect on bearing capacity. The study comprised a field model study and soil columns have been constructed by hand mixing method using cement, bentonite, mining sand and calcium chloride. Hand operated cone penetrometer has been used to observe the bearing capacity of stabilised column after 14 days curing time. Microstructure of soil column has also been observed by performing SEM and EDX test. From the study it was found that bearing capacity peat can be improved considerably by stabilised column using binder.